Americas Past and Promise - Mason, Lorna (Evanston McDougal Littell, 1997)
This bok deals primarily with this nations past. Yet you, its reader, represent the future promise of America. We hope that by knowing Americas past, you will help fulfill Americas promise.
Keywords: History